2017
DOI: 10.1007/s00508-017-1200-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical role of von Willebrand factor in acute ischemic stroke

Abstract: Among the patients with ischemic stroke, levels of VWF were not increased in those with CE stroke. High levels of VWF were associated with greater severity of stroke as well as with poor clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
6
18
0
Order By: Relevance
“…One possible explanation is that the postoperative assessment of the vWF profile was performed too early after MCS implantation. However, others have demonstrated that AvWS persists for at least 12 months after LVAD implantation, but normalized after HTx . Together, these earlier data and our results of pre‐existing changes in the vWF profile support the assumption that the changes are disease‐related and not markedly influenced by MCS implantation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One possible explanation is that the postoperative assessment of the vWF profile was performed too early after MCS implantation. However, others have demonstrated that AvWS persists for at least 12 months after LVAD implantation, but normalized after HTx . Together, these earlier data and our results of pre‐existing changes in the vWF profile support the assumption that the changes are disease‐related and not markedly influenced by MCS implantation.…”
Section: Discussionsupporting
confidence: 87%
“…It has been assumed that AvWS may play a major role in bleeding complications, including gastrointestinal bleeding, but evidence remains circumstantial . In addition, previous reports suggest a crucial role in thromboembolic strokes and hemostatic complications . However, data on the correlation of stroke, AvWS, and MCS are scarce .…”
Section: Discussionmentioning
confidence: 99%
“…An association between vWF levels, the risk of first-ever ischaemic stroke, 33 34 stroke recurrence, 35 stroke severity, 36 37 post-stroke morbidity 38 39 and mortality 40 has been reported by several studies ( Table 1 ; Supplementary Table S1 and S2 , available in the online version). Many of them were observational and case–control studies, which investigated vWF levels by use of various assays at the time of the acute ischaemic event.…”
Section: The Role Of Von Willebrand Factor In Stroke—insights From Epmentioning
confidence: 86%
“…vWF is physiologically involved in hemostatis and platelet adhesion (Luo et al 2012), and in the context of TIA/minor stroke, has been viewed as a marker of endothelial dysfunction (Lip andBlann 1997, Wieberdink et al 2010). Previous studies have demonstrated a relationship between higher levels of vWF and transient ischaemic attack and stroke (Qizilbash et al 1997, Bongers et al 2006, Lip et al 2006, Menih et al 2017. In a prospective study, Wieberdink et al (2010) found elevated plasma levels of vWF to be a prognostic biomarker of stroke risk in patients >55 years of age who were stroke-free at baseline assessments.…”
Section: Discussionmentioning
confidence: 95%